THE IMPORTANCE OF OCCUPATIONAL THERAPY IN THE SCHOOL CONTEXT - Vieira Góis dos Santos, Thais (Health and Society, 2025)
Occupational Therapy in the school context plays a fundamental role in promoting the integral development of students, contributing to inclusion, learning, and active participation in educational activities. This article aims to discuss the importance of the occupational therapist’s role in the school environment, highlighting their contributions to the teaching-learning process and to overcoming barriers that hinder students’ occupational performance. This is a bibliographic study, based on scientific productions that address the interface between Occupational Therapy and Education. The results show that the occupational therapist’s intervention favors the adaptation of teaching materials, the organization of the school environment, the development of motor, cognitive, and socio-emotional skills, as well as support for students with learning difficulties, disabilities, or developmental disorders. Furthermore, the importance of collaborative work between occupational therapists, teachers, administrators, and families is emphasized, aiming at the construction of inclusive and accessible educational practices. It is concluded that Occupational Therapy in the school context is essential for promoting equity, autonomy, and the full development of students, strengthening inclusion and the quality of the educational process.